Calorimetric Label Based On Teak And Ketapang Leaf Extracts As A Freshness Detector For Ground Beef - Surya Christien Manurung; Arina Sabrina; Diana Rizki Putri; Khoirum Fahra Della (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This research aims to prove the effectiveness of colorimetric labels based on teak leaf and ketapang leaf extracts as freshness detectors for ground beef. Methodology: The study was conducted through 3 stages, namely characterisation of natural extracts, manufacture of colorimetric labels and determination of the effectiveness of colour change of colorimetric labels. Characterisation of extracts through pH, TPT and RGB value test using image J software. The effectiveness of label colour change through colour test (L*, a*, and b*). The colour change was adjusted to the quality change of pH, total acid, and beef colour. Results: The pH, and colour values of teak leaves of 3.42; 81.17 were greater than ketapang leaves of 2.64 and 42.06. The TPT (̊ Brix) value of teak leaf extract (3.00) was lower than ketapang leaf extract (4.95). The results of colour parameter analysis L*, a*, and b* of teak and ketapang leaf colorimetric labels had no significant effect between 0, 3, and 6 hours. Ground beef experienced significantly different pH and total acid quality changes during storage with final values of 5.29 and 0.82%. Novelty: Research on the concept of colorimetric labels as freshness indicators based on pigments from teak leaves and ketapang leaves has not been widely studied, and this study shows the effectiveness of label colour changes with Whatman No. 1 paper carriers. Conclusion: The results showed that colorimetric labels based on old teak leaves and ketapang leaves were not effective in detecting the state of ground beef. Optimisation of the extraction method or the use of a different type of carrier is required. Paper Type: Research article